The adoption of mobile augmented reality in tourism industry: Effects on customer engagement, intention to use and usage behavior - Song Bee Lian; Devinder Kaur; Muthaloo Subramaniam; Poh KiongTee; Ling Chai Wong; Nor Azrul Mohd Zin (the Center for International Scientific Research, 2024)
The purpose of this study is to examine the consumer adoption of mobile augmented reality (AR) in the tourism industry in Malaysia. Drawing on the extended Technology Acceptance Model (TAM), interactivity, vividness, and information content factors are examined in relation to perceived usefulness (PU). and perceived ease of use (PEOU). Subsequently, both PU and PEOU are hypothesized towards customer engagement (CE), behavioral intention to use (BIU) and usage behavior (UB). The study consists of 500samples from consumers who have experienced the usage of mobile AR in the tourism industry in Malaysia. Using a quantitative approach, structural equation modeling (SEM) was applied to analyses the collected data. The findings revealed that interactivity, vividness and information content have positive effects on the PU and PEOU. PU and PEOU have positive effects on the CE, BIU and UB. In theoretical contributions, the study contributes to the extension of TAM by adding interactivity, vividness, and information content as antecedents to PU and PEOU. This research also validated CE as the new dimension for consumer behavioral engagement that affects BIU and Ubin the extended TAM. In practical contributions, the findings will assist tourism providers in strategic marketing planning and formulation to enhance mobile AR.